LEVELS OF DNA DAMAGE IN CRAYFISH HEMOCYTES (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
The genotoxicity of water pollution in Lake Sevan, near the Sevan peninsula, village Shorja and its basin (rivers the Gavaraget and the Dzknaget) was investigated. An assessment of DNA integrity in hemocytes of crayfish (Astacus leptodactylus) was performed using the Comet assay. The obtained results of DNA damage level of crayfishes from the aquatic environment near village Shorja, the Gavaraget and the Dzknaget Rivers demonstrate significantly higher levels than from the peninsula of Lake Sevan. The results suggest that crayfishes are sensitive test objects for ecotesting of natural water bodies.
Keywords: Comet assay, genotoxicity, crayfish hemocytes, pollution of water bodies